Laser Capture Microdissection - A Breakthrough Technology in Head and Neck Diagnostics (Bangladesh Journal of Medical Science, 2023)
Laser capture microdissection (LCM) is a technique in which, from a heterogenous tissue specimen some pure cell populations are isolated. This procedure can capture and target the desired number of cells that are required. A low energy laser pulse is used in this technique. Apart from systemic applications LCM can also be applied in the field of dentistry and pathology.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.58-62